Stunting among toddlers in poor Indonesian households - Bela, Sarni Rante Allo; Fatiah, Mona Safitri; Tambing, Yane; Laksono, Agung Dwi; Wulandari, Ratna Dwi; Kusumawardani, Hastin Dyah; Hidayat, Taufiq (Intelektual Pustaka Media Utama, 2025)
Poverty has a significant impact on stunting in children under the age of five from low-income families, accounting for around 18.4% of stunting cases in Indonesia. The goal of this study was to look into the factors that may contribute to the prevalence of stunting among children under the age of five from low-income families in Indonesia. The study used a cross-sectional design and data from the 2022 Indonesian National Nutrition Status Survey to evaluate approximately 112,574 children. The data was analyzed at the multivariate level in binary logistics using SPSS 26 software. The data revealed that around 24.8% of disadvantaged households in Indonesia experienced stunting, with a variety of variables impacting its frequency. These included residence variables (AOR:1.08 and 95% CI:1.08-1.09), maternal age (AOR: 1.28 with 95% CI: 1.21-1.25), education level (AOR: 1.02 and 95% CI: 1.01-1.03), marital status (AOR:1.02 with 95% CI: 1.01-1.03), Antenatal Care (ANC) (AOR:1.45 with 95% CI: 1.44-1.47), age of the child (AOR:3.29 with 95% CI: 3.27-3.31), and the sex of the infant (AOR:3.29 with 95% CI: 3.27-3.21). Seven characteristics have been identified as predictors of stunting in children under the age of five in disadvantaged Indonesian homes. Expanding targeted programs for low-income families is critical for increasing their income through comprehensive entrepreneurship training and social assistance activities.